Morphological Characteristics of Coral Reefs in the Marine Waters of South Buton Regency - Kusrini, Kusrini; Aba, La; Jumiati, Jumiati; Nurdianingsih, Neneng (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Coral reef ecosystems represent one of the most diverse marine systems and play a fundamental role in maintaining the ecological stability of coastal environments. Despite their importance, detailed information on coral species composition and morphological characteristics in many Indonesian coastal areas remains limited, including in the Bahari waters of Sampolawa District, South Buton Regency. This study aimed to examine coral species composition, analyze their distribution across different substrate types, and interpret the ecological implications of their morphological characteristics. Field surveys using a descriptive–exploratory approach. Data were collected through the Line Intercept Transect (LIT) method along a 50 m transect line in shallow intertidal waters. Coral colonies intersecting the transect were documented and identified based on morphological traits using the Coral Finder Toolkit Indo-Pacific 3.0. The results recorded a total of 10 coral species belonging to five families: Acroporidae (50%), Agariciidae (20%), and Fungiidae, Leptastreidae, and Merulinidae (each 10%). Species distribution varied across substrate types, with rocky sand supporting the highest species richness (70%), followed by sandy substrates (50%), while seagrass–sand substrates supported only a limited number of species (10%). The dominance of branching corals, particularly from the genus Acropora, indicates environmental conditions characterized by high light availability and relatively stable substrates, while the occurrence of solitary forms such as Fungia reflects adaptive strategies to unstable sedimentary environments. These findings highlight a clear relationship between coral morphology, substrate stability, and environmental dynamics in intertidal reef systems. This study provides baseline ecological information on coral composition and morphology in the Bahari coastal waters and emphasizes the importance of substrate characteristics in shaping coral community structure. The results can support future coastal management and coral reef conservation strategies in South Buton Regency.